H-mode WEST tungsten divertor operation: deuterium and nitrogen seeded simulations with SOLEDGE2D-EIRENE. (August 2017) - Ciraolo, G.; Bufferand, H.; Bucalossi, J.; Ghendrih, Ph.; Tamain, P.; Marandet, Y.; Valentinuzzi, M.; Denis, J.; Fedorczak, N.; Hodille, E.; Mellet, N.; Pegourie, B.; et al.
Highlights: Simulations of WEST H-mode divertor scenarios have been performed with SOLEDGE2D-EIRENE. With nitrogen seeding, lower plasma temperatures at the target plates are achieved together with the required high heat fluxes. Investigation of divertor geometry and the impact of vertical vs horizontal target plates on neutrals spreading. Abstract: Simulations of WEST H-mode divertor scenarios have been performed with SOLEDGE2D-EIRENE edge plasma transport code, both for pure deuterium and nitrogen seeded discharge. In the pure deuterium case, a target heat flux of 8 MW/m 2 is reached, but misalignment between heat and the particle outflux yields 50 eV plasma temperature at the target plates. With nitrogen seeding, the heat and particle outflux are observed to be aligned so that lower plasma temperatures at the target plates are achieved together with the required high heat fluxes. This change in heat and particle outflux alignment is analysed with respect to the role of divertor geometry and the impact of vertical vs horizontal target plates on neutrals spreading.